2021
DOI: 10.3390/ani11061791
|View full text |Cite
|
Sign up to set email alerts
|

Unmitigated Surgical Castration in Calves of Different Ages: Electroencephalographic and Neurohormonal Findings

Abstract: Castration is a common management procedure employed in North American cattle production and is known to cause a pain response. The present study was designed to investigate the effect of unmitigated surgical castration on the electroencephalography (EEG) responses and plasma substance P (SP) concentrations in calves of different ages under the same experimental conditions. Thirty male Holstein calves in three age categories [<6 weeks (6W); 3 months (3M); 6 months (6M); 10 calves per age group] were used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…This study characterized the acute physiological responses to unmitigated surgical castration in calves of varying ages, specifically cortisol concentration, heart rate variability, and changes in eye temperature, with the ultimate goal of supporting pain mitigation strategies for routine management practices like castration. Additional outcomes are reported in Bergamasco et al [ 21 ], a companion paper that can be referred to for further information. Despite the fact that surgical castration is a painful procedure having both acute and chronic impacts, the use of pain control is not routinely practiced in the United States [ 1 , 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This study characterized the acute physiological responses to unmitigated surgical castration in calves of varying ages, specifically cortisol concentration, heart rate variability, and changes in eye temperature, with the ultimate goal of supporting pain mitigation strategies for routine management practices like castration. Additional outcomes are reported in Bergamasco et al [ 21 ], a companion paper that can be referred to for further information. Despite the fact that surgical castration is a painful procedure having both acute and chronic impacts, the use of pain control is not routinely practiced in the United States [ 1 , 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research reported here was part of a large study reported in a companion paper [ 21 ] and therefore the experimental design and sampling methods are as described in that study. This research was approved by the Institutional Animal Care and Use Committee at Kansas State University (Protocol #2831).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations